Application of a CO2-stripping system for calcium removal to upgrade organic matter removal and sludge granulation in a leachate-fed EGSB bioreactor - Lu, Xueqin; Chen, Shanping; Luo, Jinghuan; Qian, Guangren; Liu, Jianyong; Zhen, Guangyin; Li, Yu-You (RSC advances, 2016)
The application of CO2-stripping system for calcium removal to upgrade organic matter removal and sludge granulation in a leachate-fed EGSB bioreactor was evaluated. Three-dimensional excitation-emission matrix (3D-EEM) spectroscopy combined with parallel factor (PARAFAC) analysis was used to characterize the transformation of the effluent dissolved organic matter (DOM) during the operation. X-ray diffraction (XRD), Fourier-transform infrared (FT-IR) and scanning electronic microscopy (SEM) were used to assess the effects of a CO2-stripping unit on the microstructure of the granules. The introduction of the CO2-stripping system reduced the calcium concentration while upgrading methane evolution. The methane yield reached 0.33 L CH4 per g CODremoved in the bioreactor with the CO2-stripping unit compared with 0.31 L CH4 per g CODremoved without the unit as the control. The combined system produced 80% and 50-60% chemical oxygen demand (COD) and total nitrogen (TN) removal under steady-state conditions, which were 6.3% and 41.0% higher than those of the control, respectively. With 3D-EEM-PARAFAC analysis, three fluorescence components, associated as tryptophan protein-like (component 1, Ex/Em = 275-280/355-365 nm) and humic-like substances (component 2, Ex/Em = 240(295, 340)/450 nm and component 3, Ex/Em = 320/320 nm), were identified from the effluent samples. The componential characterizations confirmed the favorable influence of the CO2-stripping unit on the transformation of DOM. Further analysis through XRD, FT-IR and SEM demonstrated that the use of the unit alleviated inactivation of the granules through removing calcium, which might be the core reason for the enhancement of the EGSB performance.